Distribution of heavy metals in Gasing River, South Sumatra, Indonesia - Izromaita; Ibrahim, Eddy; Suheryanto; Wildayana, Elisa (Journal of Degraded and Mining Lands Management, 2025)
The environment consists of land, the earth's atmosphere, and air. Air quality is a measure of air conditions relative to the needs of one or more biotic species. The results of the air quality analysis obtained cloudy water at sampling points 1-5, parameters below class II water quality standards are found in pH parameter at points 6-15, DO parameter at all points, BOD parameter at all points, COD parameter at points 4-6, TSS parameters at points 1-5 and 7, while the temperature and TDS parameter are still below the quality standards at all sampling points. The results of heavy metal measurements obtained Pb parameter at all points, Cu parameter at points 4-15, Cd parameter at point 7, Fe parameter at all points, Mn parameter at points 1-3 and 6-15, while the Cr parameter is still below the quality standards at all sampling points. Point 8 obtained an index value of 5.13, which means moderate pollution, while points 1 to 7 and points 9 to 15 were lightly polluted.